math , help,algebra
posted by jasmine20 .
i am up to this point in my problem but i don't know what to do next with it can someone show me.
Directions: Simplify by combining like terms
x radical(18) minus 3radical(8x^2)
these are the steps that i've done so far.
= x radical (2*9) -3radical (2*4*x^2)
= x radical (2) * radical (9) - 3 radical (2) * radical (4) * radical (x^2)
=x * radical (2) * 3 - 3*radical (2) * 2 * x
from here i do not know can someone help me finish.
You are so close
=-3x√2 or -3√2*x